The Effect of the Interaction between the Type of Learning Environment (Face to Face - Online) And the Type of Test (Essay - Bubble Sheet) on The Results of Academic Achievement among Students of Obour Institutes - Hassan Awad Elgendy; Zeyad Aly Khalil (International Journal of Instructional Technology and Educational Studies)
The aim of the current study is to investigate the effect of the interaction between the type of learning environment (face-to-face-online) and the type of test (essay-bubble sheet) on the results of academic achievement. The study sample was distributed to the second-year students of the Management Information Systems division in the course "Principles of Statistics", one of which is taught in a traditional learning environment (face to-face) and the second is taught in an electronic learning environment via the Internet (online), and two types of tests were applied (essay and bubble sheet) for each group after the completion of teaching the course, and the results were analyzed. The results of the study resulted in the superiority of the students of group (2), which was taught in a learning environment (face to-face) and was tested with a type of test (objective with the bubble sheet system), followed by group (4), which was taught in an online learning environment and was tested With a test type (bubble sheet), then group (1), which was taught in a learning environment (face to face) and was tested with a test type (Essay), and finally group (3), which was taught in an (online) learning environment. Test it with a test type (Essay).